Analyzing the Potential Impact of Docked Bikeshare on Transit First-Last Mile Accessibility in East Los Angeles - James Huang; Marlon G. Boarnet (Findings)
We model how docked bikeshare can improve transit accessibility in two Los Angeles neighborhoods. We measure the fraction of study area population within 5- and 10-minute walk/bike commutes from high frequency transit (≤ 10-minute morning peak headway). We show that bikeshare can increase the number of residents within 5-minutes / 10-minutes of high frequency transit by 12% / 13% (deploying 74 docked bikeshare stations) and by 42% / 66% (deploying 296 bikeshare stations.) The results for within the 5-minute travel time are robust to siting specification changes, while the 10-minute results are more sensitive to specification.